North-South technology spillovers: the relative impact of openness and foreign R&D - Maurice Schiff; Yanling Wang (Institute for the Study of Labor (IZA), 2008)
This paper examines the relative contribution of openness and the R&D content of trade to TFP growth for North-South trade-related technology diffusion. The measure of foreign R&D used in the literature on trade-related technology diffusion imposes identical contributions of openness and the R&D content of trade to TFP. We allow these contributions to differ and show that openness has a greater impact on TFP growth than R&D. These results imply that the impact of openness on TFP in developing countries is larger than previously obtained in this literature. In other words, developing countries can obtain larger productivity gains from trade liberalization than previously thought.
Keywords: F10; 330; Technology diffusion; R&D; openness; North-South; Technologietransfer; Spillover-Effekt; Nord-Süd-Beziehungen; Politik der offenen Tür; Forschung; Außenhandel; Produktivität; Wirtschaftswachstum; Entwicklungsländer